Gender segregation in vocational education and occupations in the context of digitalisation - Andrea Leitner; Margareta Kreimer; Ines Heck; Zora Vakavlieva (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2023)
Austria is one of the countries with persistently high gender segregation in combination with a high matching of training and occupations. In this context, we analyse how educational and occupational segregation interact in the male-dominated fields of science, technology, engineering, and mathematics (STEM) and in the female-dominated areas of education, health and welfare (EHW). We discuss how atypical education can reduce gender segregation in the labour market and whether automation risks affect women and men in STEM and EHW differently. Firstly, our analysis shows that educational segregation is heavily transmitted to the occupational system in this fields. Secondly, the results point to the potential of gender-atypical fields for reducing segregation but also to their limitations especially since we find a double mismatch for women in STEM. Based on findings from digitalisation and automation research, we find that women are overrepresented in STEM jobs focussing on manual routine tasks which are more likely to be automated than the jobs primarily performed by men. While EHW is less prone to automation in general, the distribution of tasks between men and women indicates vertical segregation despite EHW being a female-dominated sector. – – Österreich zählt zu den Ländern mit anhaltend hoher Geschlechtersegregation, gleichzeitig zeigt sich eine hohe Übereinstimmung zwischen fachspezifischen Berufsbildungsabschlüssen und Berufstätigkeit. Vor diesem Hintergrund wird die Frage untersucht: Wie interagieren das Berufsbildungssystem und die berufliche Segregation in zweistark segregierten Bereichen des Arbeitsmarktes? Mit dem Fokus der Analyse auf die männerdominierten Bereiche Mathematik, Informations- und Kommunikationstechnologie, Naturwissenschaft und Technik (MINT) einerseits und die frauendominierten Bereiche Bildung, Gesundheit und Soziales (BGS) andererseits verfolgen wir das Ziel, Geschlechtersegregation auf einer konkreten inhaltlichen Ebene zu diskutieren. Unsere Analysen zeigen erstens, dass sich Bildungssegregation in hohem Ausmaß auf das Berufssystem überträgt. Die Ergebnisse zu Frauen in MINT und Männer in BGS verweisen zweitens auf ein gewisses Potential geschlechtsuntypischer Ausbildungen und Berufe in Richtung Abbau der Segregation, zugleich aber auch auf deren Grenzen insbesondere bei Frauen in MINT. Darauf aufbauend, und unter Bezugnahme auf bisherige Erkenntnisse aus der Digitalisierungsforschung, können drittens Schlussfolgerungen zum zukünftigen Potential in STEM und EHW gezogen werden.
Keywords: 330; gender segregation; occupational segregation; vocational education; STEM subjects; mismatch; digitalisation; Geschlechtsspezifische Segregation; Berufliche Segregation; Berufsbildungssystem; Mint-Fächer; Mismatch; Digitalisierung